Polityka finansowa państwa wobec rodziny (wybrane zagadnienia) - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 1985)
A social differentiation of families in Poland is effected i.a. by the decrease of real incomes, increase of prices, exhaustion of savings. Impossibility to maintain the previous levels of living standard, that is a drop in living standard, actualizes a problem of the State financial policies towards family. A State cannot fail in being engaged in any financial phenomena which can influence living conditions and a development of a society and by virtue of that, of a family. Instituting consciously a specific system of financial matters and shaping it into a form of policy, a State tends to realize certain socioeconomic tasks towards family. General goals of State policies in that aspect cannot be formed in the domain of finances, these can only create special tools to implement the said goals. As they cannot be the sole tools used by the State, they must be selected in order to be compatible with the effect of other means used. The effect of financial policies of State towards family has to be estimated in the context of ruling the level of its purchasing fund. It is ruled by the whole set of factors being interrelated e.g. earnings, social benefits, indirect taxes, direct taxes, payments, tarriffs, prices, credits and savings. It is significant that instruments of indirect intervention, instead of the direct one, formally concerning other subjects than a family are gaining a higher rank in the State financial policies towards family.
State financial policies towards family